Factor Structure of Urdu Version of the Flourishing Scale - Choudhry, Fahad R.; Al-Worafi, Yaser M.; Akram, Bushra; Ahmed, Mirza A.; Anwar ul Haq, Muhammad; Khan, Tahir Mehmood; Rehman, Inayat U.; Barki, Nadia; Munawar, Khadeeja; Kamal, Anila; Kassab, Yaman W.; Bakrin, Faizah S.; et al. (Frontiers in Psychology, 2018)
Background A great deal of research has been carried out on the assessment of the eudaimonic perspective of psychological well-being and the hedonic perspective of subjective well-being. The Flourishing Scale (FS) has been extensively used in research and practice, as it assesses fundamental aspects of social-psychological functioning. Nevertheless, the psychometric properties of the Urdu version of eudaimonic measures, such as the FS have not yet been ascertained. The translation and validation of the FS in the Urdu language is not available, thus this study was planned with the aim to validate the Urdu version of the FS. Methods We assessed the psychometric properties of the FS in a sample of adults aged 18 years and above in Pakistan (N = 130) using exploratory factor analysis (EFA) based on Principal Component Analysis with Varimax Rotation and Confirmatory Factor Analysis (CFA). Results The CFA revealed a good fit model. Also, the EFA confirmed the unidimensional nature of the FS. We assessed that the Urdu version of the FS showed a high internal consistency reliability (α = 0.914) with a significant intraclass correlation coefficient p < 0.001). In our study, the KMO value was 0.915 with a Chi-Square value (χ2 = 637.687), and Bartlett’s test of sphericity was significant (df = 28, p < 0.001). The intraclass correlation coefficients (ICC) at test re-test for all domains were statistically significant (p<0.001) and showed excellent agreement for all the items. Conclusions The findings suggest that the FS is a psychometrically sound instrument for assessing social-psychological functioning among adults in Pakistan. Therefore, the validated Urdu version of the FS may be used in future studies of well-being in clinical psychology and positive psychology. Keywords: Psychometric properties, Confirmatory factor analysis, Mental well-being, Psychological well-being, Social-psychological functioning, Flourishing